ANALISIS HUBUNGAN ANTARA KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN TERHADAP KEINGINAN PEMBELIAN ULANG, STUDI KASUS DI UNIVERSITAS BUNDA MULIA - YB Andre (Business Management Journal, 2017)
The purpose of this research is to obtain a better understanding of the relationship among customer satisfaction and customer loyalty to repurchase intention. One of the methods used in this paper is by surveying students (as customers) from 12 departements in Bunda Mulia University (UBM). The students have to fill in the questionnaires related to customer satisfaction, customer loyalty and repurchase intention concepts. A total of 232 students filled the questionnaires. The results support the conceptual model in demonstrating a strong relationship among customer satisfaction and customer loyalty to repurchase intention. One of the findings shows that the dimension of satisfaction does not directly support repuchase intention. This research adds to the body of knowledge related to customer satisfaction management.Keywords : Consumer satisfaction, repurchase intention